The Conflict of Role and Sign: A Zoosemiotic Approach on Long-tailed Macaque in Bali - Putu Bayu Wikranta Kusuma Jaya (Pelopor Publikasi Akademika, 2023)
Zoosemiotics as a system of signs that occurs between animals, presents the initial premise that their existence is no longer purely biological, but vulnerable to the influence of human cultural life. This research examines the survival instincts of long-tailed macaques in a zoosemiotics approach, focusing on the need for food, and the reaction to threats. Data were collected through direct observation and unstructured interviews in two spatial distinctions, namely a natural location and an artificial location. Data analysis was carried out in an interpretive-qualitative manner. The results showed that Long-Tailed Macaques in the artificial location reacted very little to threat, in contrast to those in the natural location. Meanwhile, the need for food from long-tailed macaques in the natural location does not cause interspecies conflict as occurs in the artificial location. The influence of human cultural life has reduced long-tailed macaques' formerly more independent and purely biological survival instincts